Sex and survival outcomes in patients with renal cell carcinoma receiving first-line immune-based combinations - Incorvaia, Lorena; Monteiro, Fernando Sabino Marques; Massari, Francesco; Park, Se Hoon; Roviello, Giandomenico; Fiala, Ondřej; Myint, Zin W; Kucharz, Jakub; Molina-Cerrillo, Javier; Santini, Daniele; Buttner, Thomas; Poprach, Alexandr; et al. (Cancer immunology and immunotherapy, 2024)
BACKGROUND: There is an ongoing debate as to whether sex could be associated with immune checkpoint inhibitor (ICI) benefit. Existing literature data reveal contradictory results, and data on first-line immune combinations are lacking. METHOD: This was a real-world, multicenter, international, observational study to determine the sex effects on the clinical outcomes in metastatic renal cell carcinoma (mRCC) patients treated with immuno-oncology combinations as first-line therapy. RESULTS: A total of 1827 mRCC patients from 71 cancer centers in 21 countries were included. The median OS was 38.7 months (95% CI 32.7-44.2) in the overall study population: 40.0 months (95% CI 32.7-51.6) in males and 38.7 months (95% CI 26.4-41.0) in females (p = 0.202). The median OS was higher in males vs. females in patients aged 18-49y (36.9 months, 95% CI 29.0-51.6, vs. 24.8 months, 95% CI 16.8-40.4, p = 0.426, with + 19% of 2y-OS rate, 72% vs. 53%, p = 0.006), in the clear cell histology subgroup (44.2 months, 95% CI 35.8-55.7, vs. 38.7 months, 95% CI 26.0-41.0, p = 0.047), and in patients with sarcomatoid differentiation (34.4 months, 95% CI 26.4-59.0, vs. 15.3 months, 95% CI 8.9-41.0, p < 0.001). Sex female was an independent negative prognostic factor in the sarcomatoid population (HR 1.72, 95% CI 1.15 - 2.57, p = 0.008). CONCLUSIONS: Although the female's innate and adaptive immunity has been observed to be more active than the male's, women in the subgroup of clear cell histology, sarcomatoid differentiation, and those under 50 years of age showed shorter OS than males.
Keywords: senioři; Carcinoma, Renal Cell; senioři nad 80 let; Immune Checkpoint Inhibitors; Prognosis; lidé; mladiství; sexuální faktory; Middle Aged; mužské pohlaví; karcinom z renálních buněk; míra přežití; Adult; mladý dospělý; Kidney Neoplasms; inhibitory kontrolních bodů; Aged, 80 and over; Young Adult; ženské pohlaví; prognóza; imunoterapie; Humans; Sex Factors; Survival Rate; lidé středního věku; Immunotherapy; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; Adolescent; nádory ledvin; Male